Ranking of Leadership Styles and National Culture Factors Affecting Smart Government Organizational Performance - Ibrahim Almansoori, Khalid Abdulla; Ahmad, Ahmad Nur Aizat (International Journal of Sustainable Construction Engineering and Technology, 2023)
Investigating leadership style, organisational performance, and national culture indicators in Abu Dhabi, the smart-government capital of the UAE was carried out through quantitative method of research. Total 274 valid data samples were gathered and analysed with SPSS software to perform descriptive assessment. Reliability test revealed that all the indicators have Cronbach Alpha value above 0.7 confirming the validity of the data. Skeweness and Kutosis values of the parameters showed that the data follows normal distribution. Employee morale and satisfaction were cited as the most critical parameters for gauging organisational performance, while the study found that personal steadiness and stability is the most desired parameters of national culture. All four of the leadership styles that were studied were deemed significant. Based on responses, "my supervisor makes others feel good to be around him/her" is the most important aspect of a transformational leader, while "my supervisor tells others what to do if they want to be rewarded for their work" is the most important aspect of a transactional leader. Among the parameters studied, "As a rule, my supervisor allows me to appraise my own work" ranked highest in accordance with Laissez Faire Leadership, while "Do you agree that the Authoritative leadership style employed by your supervisor contributes to your feelings of insecurity in your work and the need for clear direction?" ranked highest in accordance with Authoritative Leadership. These finding pointed out that the designed parameters can be used for further study related to national culture, organizational performance and leadership styles adopted in UAE in relation with Smart government.